Microvertebrates preserved in mammal burrows from the Holocene of the Argentine Pampas: a taphonomic and paleoecological approach - Tomassini, Rodrigo Leandro (2017)
Microvertebrates are a major component of many assemblages recovered from the Quaternary of the Argentine Pampas. The main goal of this paper is to analyse the taphonomic history of a Holocene microfossil bonebed, recovered from the infilling of a burrow. Evidences suggest the plains vizcacha Lagostomus maximus as the putative producer of the burrow. The assemblage includes individuals belonging to different taxa of mammals (marsupials and rodents) and reptiles (snakes). Taphonomic features suggest that the accumulation inside the burrow was related to flooding processes in the plain. The burrow was a natural trap that favoured the accumulation and preservation of remains corresponding to individuals from different sources. According to the taphonomic evidence, some individuals (Lagostomus maximus, Lestodelphys halli and Serpentes indet.) died inside the burrow, whereas others (Microcavia australis, Reithrodon auritus and Ctenomys sp.) died outside the burrow, and after a time of being exposed on the surface their remains were transported by surface run-offs into the burrow. The record of Lestodelphys halli and Serpentes indet. in the burrow produced by Lagostomus maximus could be related to a circumstantial use. Mammal burrows are a significant taphonomic mode for the late Cenozoic of the Argentine Pampas.